THE DYNAMICS OF LOCAL GOVERNMENT IN ADOPTING ACCRUAL BASIS SYSTEM (STUDY CASE OF DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN OF PONTIANAK CITY) - Citra, Citra Ayu Awalia B1034131007 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT This study discovers the experiences about a reporting sytem change (accrual based accounting system) of a regional apparatus work units (SKPD) in Local Government of Pontianak City, with the reasearch site is Dinas Perumahan dan Kawasan Permukiman of Pontianak City. The study also draws attention to the institutional capacity of the Pontianak Local Government and implementation problems encountered in adopting an accrual accounting system. This study employed a case study approach with qualitative research method. The sources of data in this study are primary source of data such as direct observation, interviews, and documentation. This study uses institutional theory in conceptualising how an accounting changes has been undertaken. The study shows that the change of the reporting system inflicts some obtacles. There are also many technical and insitutional problems that happend during the implementation especially in the introduction period and at the first implmentation period, such as the lack of human resources availability, short training by the local government and the infomration system problems. However, based on the experience of Dinas Perumahan dan Kawasan Permukiman of Pontianak City in implementing the new accounting system, even they faced some problems during the implementation, they can survive and face the problem, they do self learning to understand the new accounting standard, and they have technical assistance who can help them if they have any problems related with the implementation of the new accounting system.  Keyword: Accrual accounting, Indonesian local government, Accounting systems, Organizational change, Accounting research